Preços relativos e política monetária no Brasil: Uma discuss\~ao a partir do Índice de Contribuiç\~ao para o Desvio da Meta de Inflaç\~ao (ICMI) e da desagregaç\~ao do IPCA por natureza dos produtos - Thiago Sevilhano Martinez (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The objective of this paper is to present the contributions of different sectors to deviations of the inflation target center from 2000 to 2013, and discuss implications for monetary policy. The contributions are measured by the Inflation Targeting deviation Contribution Index (ITCI), which is an enhanced version of the index presented in Martinez and Cerqueira (2013). ITCI is applied to a disaggregation by type of product of the National Consumer Price Index (IPCA), in three levels. The observed trends, particularly the recent rise in services inflation, are discussed in the light of the new-Keynesian literature on optimal monetary policy under sectorial heterogeneity in price rigidity.
Keywords: E31; E52; E64; 330; relative prices; optimal monetary policy; inflation targeting; inflation decomposition; IPCA; ITCI